Optimal indication of single-incision laparoscopic cholecystectomy using Konyang Standard Method in benign gallbladder diseases - Seung Jae Lee; In Seok Choi; Ju Ik Moon; Dae Sung Yoon; Won Jun Choi; Sang Eok Lee; Nak Song Sung; Seong Uk Kwon; In Eui Bae; Seung Jae Roh; Sung Gon Kim (Journal of Minimally Invasive Surgery)
Purpose: The optimal indications for single-incision laparoscopic cholecystectomy (SILC) have not yet been established.Methods : This single-center retrospective study included consecutive patients who underwent SILC between April 2010 and June 2020. Difficult surgery (DS) (conversion to multiport or open cholecystectomy, adjacent organ injury, operation time of ≥90 minutes, or estimated blood loss of ≥100 mL) and poor postoperative outcome (PPO) (postoperative hospital stay ≥ 7 days or Clavien-Dindo grade ≥ II postoperative complications) were defined to comprehensively evaluate surgical difficulty and postoperative outcomes, respectively.Results : Of 1,405 patients (mean age, 51.2 years; 802 female [57.1%]), 427 (grade I, n = 358; grade II/III, n = 69) underwent SILC for acute cholecystitis (AC), 34 (2.4%) needed conversion to multiport (n = 33) or open cholecystectomy (n = 1), 7 (0.5%) had adjacent organ injury during surgery, and 49 (3.5%) developed postoperative complications. Of the patients, 89 and 52 had DS and PPO, respectively. In the multivariate analysis, grade I AC, grade II/III AC, and body mass index of ≥30 kg/m2 were significant predictors of DS. Age of ≥70 years and DS were significant predictors of PPO. In a subgroup analysis of patients with AC, DS (9.5% vs. 27.5%, p < 0.001) and PPO (5.0% vs. 15.9%, p = 0.001) were more frequent in patients with grade II/III AC than in those with grade I AC.Conclusion : SILC is not recommended in patients with grade II/III AC and should be carefully performed by experienced and well-trained surgeons.